2017
DOI: 10.1515/mmcks-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Corporate and supply chain network governance of third party logistics service providers: Effects on buyers’ intention to continue the relationship

Abstract: This study focuses on the impact of corporate governance, supply chain network governance and competencies such as sales and logistics competence on buyers’ intention to relationship continuity. A total number of 258 questionnaires were distributed to Turkish manufacturing firms, selected using cross-sectional sampling method from the Istanbul and Edirne Chamber of Commerce and Industry in Turkey. The data of survey was analysed using PLS-SEM model with WARP PLS 5.0 software. Our findings indicate that corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As supporting evidence, Cannon et al (2010) underscored the importance of financial performance within the buyer-supplier relationship context, with a specific focus on long-term orientation. In particular, several studies confirmed the crucial impact of economic benefits on shaping buyers' willingness to maintain a continuous relationship with their current suppliers (Hwang et al, 2013;Börteçine and _ Ismail, 2017). Hunt and Nevin (1974) asserted that relationship satisfaction within the business to business context significantly reduces the probability of buyer-supplier contracts being terminated.…”
Section: Wine Supplier Quality Attributesmentioning
confidence: 93%
“…As supporting evidence, Cannon et al (2010) underscored the importance of financial performance within the buyer-supplier relationship context, with a specific focus on long-term orientation. In particular, several studies confirmed the crucial impact of economic benefits on shaping buyers' willingness to maintain a continuous relationship with their current suppliers (Hwang et al, 2013;Börteçine and _ Ismail, 2017). Hunt and Nevin (1974) asserted that relationship satisfaction within the business to business context significantly reduces the probability of buyer-supplier contracts being terminated.…”
Section: Wine Supplier Quality Attributesmentioning
confidence: 93%
“…Bulgurcu and Nakiboglu [32] discovered that five of the most commonly cited factors for the on-demand drivers for 3PL services are costs, compatibility, IT operation and service quality, asset possession, and operational factors. To thrive and preserve their competitive ability in the market, companies must compete with one another for the opportunity to acquire the needed essential assets while offering adaptable and rapid services in the supply chain, which is feasible by using either corporate oversight or supply chain network oversight [33]. The capability of a robust transportation system, quality accreditation, safety and health, excellent service, and sustainability credentials, and other factors that need the highest consideration of corporate decision-makers, are among the most significant and inspiring of these aspects [34].…”
Section: Determinant Factors Of 3pl Services Demandmentioning
confidence: 99%
“…In terms of flow mechanisms, research to date has significantly limited the range of logistical instruments that can be used by the coordinator. Attempts related to the alignment of logistic operators with the principles of network functioning and network mechanisms have been undertaken by researchers [11][12][13]. However, none of these works present a set of characteristics that predispose logistic operators to network coordination.…”
Section: Introductionmentioning
confidence: 99%